Loan as Rural Development Support Case in Sudokarto, Godean, Sleman District DIY - S Soewadi (Universitas Muhammadiyah Surakarta, 1990)
This reseach is excecuted in Sidokarto village Godean Subdistrial, Kabupaten Sleman, special province of Yogyakarta, and is derived from the question of how rural community uses formal and in-formal failities of lend institution (credits source) that are available in their villages. Are the debts affecting the income of rural community? The aim of this research is to find out the back ground of rural community life, public choice to decide creditor, and the income of family holder. Methodology applied in the research is a surveying methode. The seletion of the region was executed in purposive sampling tehnique and the respondents were randomly selected. The respondents were the heads of family as debtors who have taken the credit from either government or private. Analysis used in this research was frequency tabulation, cross tabulation and analysis of correlation is done by using product moment technique. The result proved that most of the debtors (more than 50%) are non peasant with low-rank education (passed and dropped out of elementary schools). Among the debtors, the greater part (93.55%), have used the formal merits i.e. KUD and BRI. Debtor's choice of lend institution is in fluenced by aspect of location and the ease of service. It is proved that the more debtors live near to the lend institution, the quality of the debtors will increase. The reason why credit source is used is influenced by the question whether it is easy or not to get the debt, without taking notice of rent, although it is low enough. The result also proved that, for the greater part of debtors have used the debt money to increase the capital for non agricultural ativities.